Avaliações docentes acerca da variável "objeto direto de terceira pessoa do singular" : contribuições da sociolinguística educacional - Freitas, Rosely Lopes de (2022)
Beliefs and linguistic attitudes influence, amongst other things, the processes of variation and linguistic change, dialect accommodation, and language teaching. Furthermore, Portuguese Language (PL) teachers’ beliefs and attitudes towards Language are highly likely to influence both their perceptions regarding linguistic matters and their assessment process concerning student productions. In this setting, a sociolinguistic background for teachers is required and eventually leading to a teaching practice that can provide a broad language understanding for students, to enable them to grasp the dynamicity/heterogeneousness/systematicity in language, and that it is constituted of grammar, lexis, text rules and is also related to identity and cultural questions of a given linguistic community. Through such knowledge, students will certainly comply with linguistic respect. The present research is grounded on Variationist Sociolinguistics (LABOV, 2008), Educational Sociolinguistics (BORTONI-RICARDO, 2004), studies on beliefs and linguistic attitudes (LAMBERT, 1972; MORENO FERNÁNDEZ, 1998, SILVA, 2008), and investigations on third-person direct object variable from a diachronic perspective (CYRINO, 1994) and also oral (DUARTE, 1986) and written (AVERBUG, 2003) modalities. Thus, the general objective of the present study is to understand the influences of linguistic perceptions of PL teachers on the morphosyntactic phenomenon of the third-person direct object in the process of evaluating students' essays, to incorporate proposals for activities with this variable from the perspective of Educational Sociolinguistics. For that, we outlined four specific objectives: (i) understand teachers’ conceptions about some Portuguese teaching-related terms such as language, grammar, linguistic norm, and variation; (ii) assess teachers’ perceptions about the third-person direct object variable in varied spoken and written contexts; (iii) check the corrections performed by teachers related to third person direct object variable in a short story; (iv) develop proposals for activities to assist/encourage PL teachers in producing exercises that allow students to reflect on the variable from different perspectives. The research participants were 10 Portuguese teachers in primary and secondary education. Firstly, they were asked to answer a three-part form on Google Forms: (1) Statements on teaching practice; (2) Opinion on general terms in Portuguese teaching, and (3) Assessment of the four variants of third person direct object variable in three spoken and written contexts. Later, the teachers were asked to correct a short story, specifically, the linguistic variable in question. After data analysis, we found that a) as for the perception test, the clitic accusative variant (CA) was mostly associated with the “excellent” attribute. On the other hand, lexical pronoun (LP), the least associated with that attribute and regarded as “bad”; b) regarding the corrections in the text, we found that the LP was the most corrected variable, followed, in descending order, by the CA and variants regarded as “neutral” (noun syntagm and null object); c) concerning the suggestions of variant substitutions, broadly speaking, teachers suggested that the student/writer of the short story substituted the variants for the CA. Therefore, it was seen that for the participating teachers, CA is the prestige variant; LP is stigmatized, and NO and NS are “the most neutral”. Thus, our study raises questions about the influence of linguistic perceptions in teachers’ assessment, the importance of a sociolinguistic background for Portuguese Language teachers, and a teaching practice grounded on the principles of Variationist Sociolinguistics.